Building the future One Health workforce in Eastern and Southern Africa: Gaps and opportunities - Buke Yussuf Wako; Shauna Richards; Delia Grace; Ianetta Mutie; Alex Caron; Helene De Nys; Brighton Goregena; Moatlhodi Kgosimore; Esther Kimaro; Nenene Qekwana; Yordanos Tadesse; Theo Knight-Jones; et al. (CABI One Health)
Abstract The Quadripartite comprised of the Food and Agriculture Organization (FAO), World Health Organization (WHO), World Organisation for Animal Health (WOAH), the United Nations Environment Program (UNEP), and the One Health High Level Expert Panel collectively support enhancing the One Health (OH) capacities of the workforce addressing OH issues; however, competencies for this workforce are not generally agreed upon, applied uniformly, or always relevant in the global South. The objectives of this study were to (1) develop an inventory of OH education offered by higher education institutes in Eastern and Southern Africa, and (2) define OH competencies relevant for OH training in Eastern and Southern Africa. A survey in 11 Eastern and Southern African countries was conducted with OH key informants purposively selected from higher education institutes offering OH education (n = 1–3/higher education institutes). Snowball sampling was used to identify additional higher education institutes/individuals. Results were validated by OH country representatives. Data were collected using questionnaires, and descriptive statistics were used to present the results. Forty-two questionnaires were completed from 29 higher education institutes, and 166 OH education interventions were reported with 69% being courses contributing to a degree, 21% as degree/diploma awarding, and the remainder were missing data (n = 16). Masters were the most common OH degree program of which the highest number of students taught were from public health/OH, food safety, and applied epidemiology. There are many OH educational courses and activities on offer in Eastern and Southern Africa; however, their total breadth is difficult to assess due to limited awareness of the availability of OH education not only between higher education institutes in a country but also even within a higher education institute between faculties. Numerous cross-cutting and technical competencies were considered essential to work in OH; however, this level of expertise is rarely logistically possible to provide in any single degree program. For OH education to be consistently applied, competency frameworks that are relevant to a region are necessary. Technical competencies are important from a disciplinary context; however, necessary cross-cutting competencies should be a focus in developing the future OH workforce. One Health impact statement A One Health multisectoral approach is needed to address global health threats at the interface of human-animal-environment. The quadripartite and One Health High Level Expert Panel (OHHLEP) identified One Health education as one of the action tracks that will contribute to achieving sustainable health and food systems and reducing global health threats. The OHHELP emphasized the need to identify existing One Health initiatives and evaluate the capacities related to research and implementation, especially those focusing on the One Health workforce. This study represents efforts to understand what One Health education is available in Eastern and Southern Africa (ESA), identify competencies relevant to One Health in ESA, and assess the need for resources to integrate One Health into curricula in ESA. The study findings highlight the need for standardized One Health competencies, low awareness about available One Health programs, both between and within higher education institutes, emphasizing the need for greater information sharing and collaboration. The findings provide the relevant stakeholders and practitioners in academia with the information and tools they need to support and promote the integration of streamlined One Health education at different levels. Awareness can be created on the identified One Health programs that are available at different levels for increased adoption.